Unfolded protein stress in the endoplasmic reticulum and mitochondria: a role in neurodegeneration - Bernales, Sebastián; Morales Soto, Marisol A.; McCullagh, Emma (Frontiers in Aging Neuroscience, 2012)
Protein folding occurs in several intracellular locations including the endoplasmic reticulum (ER) and mitochondria. In normal conditions there is a balance between the levels of unfolded proteins and protein folding machinery. Disruption of homeostasis and an accumulation of unfolded proteins triggers stress responses, or unfolded protein responses (UPR), in these organelles. These pathways signal to increase the folding capacity, inhibit protein import or expression, increase protein degradation and potentially trigger cell death. Many aging-related neurodegenerative diseases involve the accumulation of misfolded proteins in both the ER and mitochondria. The exact participation of the UPRs in the onset of neurodegeneration is unclear, but there is significant evidence for the alteration of these pathways in the ER and mitochondria. Here we will discuss the involvement of ER and mitochondrial stress and the possible contributions of the UPR in these organelles to the development of two neurodegenerative diseases, Parkinson’s disease (PD) and Alzheimer’s disease (AD).